Tumbuhan dalam Ruang Sakral: Kajian Etnobotani pada Tradisi Siraman Waranggono di Sendang Bektiharjo, Tuban - Aqila Zahrotul Firdausiyah; Bilqis Marella Putri Ramadhani; Novalia Ramadhani Setyono; Fahrul Ghani Muhaimin; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to examine and document local knowledge regarding the use of plants in the Siraman Waranggono tradition in Sendang Bektiharjo, Tuban, from an ethnobotanical perspective. The research was conducted using a qualitative descriptive approach through interviews, observations, and documentation, with informants selected through purposive and snowball sampling. The results of the study indicate that the Siraman Waranggono tradition utilizes 17 plant species from 16 families, with a predominance of herbaceous (7.41%) and shrubby (6.35%) growth forms. The plant parts used include flowers, leaves, and fruits, which are utilized as ingredients in kembang telon, as ritual accompaniments, as decorations for the waranggono, and as components of offerings or ubarampe. Each plant species carries philosophical meanings related to purity, self-protection, harmony, hope for life, and community well-being. Most plants are obtained from home gardens, traditional markets, and local cultivation with a relatively secure conservation status, indicating the presence of locally-based conservation practices. Thus, this study demonstrates that the Siraman Waranggono tradition functions not only as a cultural practice but also reflects a biocultural knowledge system that integrates cultural and spiritual values, biodiversity conservation, and the community’s ethnobotanical knowledge.